A method for preparing cobalt-nitrogen-carbon material with high electrocatalytic performance

By using a mixed reaction of polyol solvent and organic ligand solution in the preparation process of cobalt nitrogen carbon material, a zeolite imidazole ester skeleton structure material was formed, and inorganic salt solution impregnation and high-temperature calcination were carried out, the problem of difficulty in dispersion and size regulation of MOFs precursors was solved, and the electrocatalytic performance of Co-N-C materials was significantly improved.

CN116093348BActive Publication Date: 2025-04-29SINOSTEEL NANJING NEW MATERIALS RES INST CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310065894.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-17
Publication Date
2025-04-29
Estimated Expiration
2043-01-17

AI Technical Summary

Technical Problem

In the prior art, the dispersion and size of the MOFs precursor of cobalt nitrogen carbon materials are difficult to regulate, affecting its electrocatalytic activity.

Method used

The cobalt salt solution is prepared by using polyol as solvent, mixed with organic ligand solution to form a zeolite imidazole ester skeleton structure material, and is decomposed by inorganic salt solution impregnation and high-temperature calcination to obtain Co-N-C material.

Benefits of technology

Through this method, the obtained Co-N-C material has a small particle size, a large specific surface area, a high pore capacity, and significantly improved electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093348B_ABST
    Figure CN116093348B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a cobalt-nitrogen-carbon material with high electrocatalytic performance, and belongs to the technical field of catalyst material preparation. The preparation method includes: (1) preparing a cobalt salt solution with a polyol as a solvent; (2) preparing an organic ligand solution, wherein the solvent used is ethanol or methanol; (3) mixing the organic ligand solution with the cobalt salt solution for reaction; (4) solid-liquid separation to obtain a zeolite imidazolate skeleton structure material; (5) impregnating the zeolite imidazolate skeleton structure material with an inorganic salt solution; (6) under the protection of an inert gas, calcining and decomposing the impregnated zeolite imidazolate skeleton structure material at a high temperature to obtain a Co‑N‑C crude product; (7) purifying the Co‑N‑C crude product, removing inorganic salts and impurities therein, and obtaining a pure Co‑N‑C powder. The cobalt-nitrogen-carbon material prepared by the preparation method has a small particle size, a large specific surface area, a high pore volume, and a high electrocatalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst material preparation, and in particular relates to a method for preparing a cobalt-nitrogen-carbon material with high electrocatalytic performance. Background Art

[0002] In clean energy, hydrogen fuel cells are energy conversion devices that directly convert the chemical energy of hydrogen (H2) into electrical energy by chemical reaction. They have the advantages of high energy conversion efficiency, high power density, small footprint, wide application range, and clean energy conversion process. They have broad application prospects in heavy trucks, public vehicles, portable electrical equipment, etc. Although hydrogen fuel cells have made unprecedented progress, there are still many problems that need to be solved urgently, one of which is the electrocatalyst used for the cathode of the fuel cell. At present, commercial electrocatalysts are mainly based on platinum-carbon catalysts, but platinum, as a precious metal, cannot meet the needs of large-scale industrialization of electrocatalysts in terms of both output and price. Therefore, the development of non-precious metal electrocatalysts is of great significance. Using non-precious metals to replace precious metal platinum can reduce costs, improve catalyst performance, and further promote the commercialization of hydrogen fuel cells.

[0003] Among the current non-precious metal systems, cobalt-nitrogen-carbon (Co-NC) catalysts are catalysts with great application prospects and commercial potential due to their large specific surface area, reasonable pore size distribution, good stability, high active site density, and methanol resistance. At present, there are four main technical routes for synthesizing Co-NC: (1) Mixing melamine / dicyandiamide with water to form a mixed solution, and subjecting the precursor to a hydrothermal reaction, and then mixing the precursor with an ethanol solution of cobalt acetate, calcining after solid-liquid separation to obtain a cobalt-nitrogen-carbon catalyst (CN114534759A); (2) Firstly, nitrogen-doped carbon carriers (C3N4, etc.) are obtained by high-temperature decomposition of precursors such as urea and melamine, and then the carbon carriers are impregnated in cobalt salt solutions such as cobalt nitrate and cobalt chloride by an impregnation method, and finally the Co-NC material is obtained by further high-temperature pyrolysis (CN106925330A ); (3) reacting acrylonitrile and cobalt chloride hexahydrate with ethyl acetate as solvent, filtering and washing after the reaction, stirring the obtained solid with colloidal SiO2 in a mixed solvent, filtering and drying, annealing in a tube furnace, and then treating with HF aqueous solution to remove SiO2 to obtain CoNC sample (CN114345387A); (4) mixing cobalt salt with ligands such as 2-methylimidazole and o-phenanthroline in ethanol and methanol solvents to form metal organic framework materials (MOFs), and then pyrolyzing MOFs at high temperature in an inert gas atmosphere to obtain cobalt nitrogen carbon (CN114713259A).

[0004] However, the above synthesis schemes all have certain problems. Scheme (1) requires a hydrothermal reaction to synthesize the precursor in the reaction. The reaction needs to be carried out in an autoclave at a reaction temperature of 160-180°C. The scaled-up preparation has high requirements for the reaction device and is not suitable for large-scale production. Scheme (2) is to first impregnate the cobalt salt precursor on a carrier with a high specific surface area and then pyrolyze it. The carrier will limit the number of active sites. Too high a loading amount will lead to uneven distribution of active sites, which is not conducive to improving catalytic activity. Scheme (3) uses a template method to prepare cobalt nitrogen carbon materials. The pore size of the cobalt nitrogen carbon can be adjusted by changing the size of the template so that its active sites can fully contact the reactants. However, the synthesis process is relatively complicated, and the HF used in the synthesis process is a hazardous chemical. Large-scale production has high requirements for operating procedures and equipment. Scheme (4) has a simple synthesis process, the obtained cobalt-nitrogen-carbon sites are evenly distributed, the specific surface area is large, and the requirements for synthesis conditions and equipment are low. It has the potential for scale-up synthesis and preparation, and is an ideal technical route for the preparation of cobalt-nitrogen-carbon. However, during the synthesis process, there are still certain problems in the regulation of the dispersion and size of the MOFs precursor, which requires further research and optimization to improve its electrocatalytic activity.

[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0006] The purpose of the present invention is to solve the problem that the dispersibility and size of MOFs precursors are difficult to control during the preparation of cobalt nitrogen carbon in the prior art, and to provide a method for preparing cobalt nitrogen carbon materials with high electrocatalytic performance.

[0007] The first aspect of the present invention provides a method for preparing a cobalt-nitrogen-carbon material with high electrocatalytic performance, comprising the following steps:

[0008] (1) preparing a cobalt salt solution using a polyol as a solvent;

[0009] (2) preparing an organic ligand solution, wherein the solvent used is ethanol or methanol;

[0010] (3) mixing the organic ligand solution and the cobalt salt solution to react;

[0011] (4) performing solid-liquid separation on the reaction system after the reaction to obtain a zeolite imidazolate framework structure material;

[0012] (5) impregnating the obtained zeolite imidazolate framework material with an inorganic salt solution;

[0013] (6) Under the protection of an inert gas, calcining and decomposing the impregnated zeolite imidazolate framework material at a high temperature to obtain a crude Co-NC product;

[0014] (7) The crude Co-NC product is purified to remove inorganic salts and impurities therein to obtain pure Co-NC powder.

[0015] In one embodiment of the present invention, in step (1), the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt bromide, cobalt acetate and cobalt sulfate.

[0016] In one embodiment of the present invention, the concentration of cobalt ions in the cobalt salt is 0.05 to 0.5 mol / L.

[0017] In one embodiment of the present invention, in step (1), the polyol is at least one selected from ethylene glycol, propylene glycol, glycerol, and butylene glycol.

[0018] In one embodiment of the present invention, in step (2), the organic ligand is selected from at least one of 2-methylimidazole and 5,6-dimethylbenzimidazole.

[0019] In one embodiment of the present invention, the concentration of the organic ligand in the solution is 0.01-0.1 g / mL.

[0020] In one embodiment of the present invention, the mixing reaction in step (3) specifically comprises:

[0021] The organic ligand solution and the metal cobalt salt solution are fully mixed by vigorous stirring for 0.5 to 1.5 hours to obtain a mixed solution, and then the mixed solution is reacted in a water bath at 60 to 80° C. for 0.5 to 4 hours.

[0022] In one embodiment of the present invention, the solid-liquid separation in step (4) is selected from at least one of centrifugal separation, vacuum filtration, and cross-flow filtration.

[0023] In one embodiment of the present invention, after the solid-liquid separation, the obtained solid zeolite imidazolate framework material is further washed with ethanol.

[0024] In one embodiment of the present invention, the solid zeolite imidazolate framework material is dried by air blast at 50-70° C. The air blast drying may be performed after solid-liquid separation or after solid-liquid separation and ethanol washing.

[0025] In one embodiment of the present invention, in step (5), the inorganic salt is selected from at least one of potassium chloride and sodium chloride.

[0026] In one embodiment of the present invention, the concentration of the inorganic salt in the solution is 0.01 to 0.1 g / mL.

[0027] In one embodiment of the present invention, the solvent of the inorganic salt solution is selected from at least one of methanol and ethanol.

[0028] In one embodiment of the present invention, the immersion treatment time is 2 to 4 hours.

[0029] In one embodiment of the present invention, in step (6), the inert gas is selected from at least one of argon, nitrogen and helium.

[0030] In one embodiment of the present invention, the high temperature calcination temperature is 800-900°C.

[0031] In one embodiment of the present invention, the purification treatment in step (7) specifically comprises: dispersing the crude Co-NC product in water, standing for 1 to 2 hours, separating the solid from the liquid, and drying.

[0032] Compared with the prior art, the technical effects achieved by the present invention are as follows:

[0033] (1) By selecting a mixed solvent of ethanol / methanol and polyols for the synthesis of Co-NC precursors, ethylene glycol and propylene glycol have a certain viscosity. After adding the reaction solvent, the migration rate of metal ions is reduced, which is beneficial to inhibit the excessive growth of crystals and avoid the obtained crystal size being too large, so that the particle size of the precursor can be stabilized in a smaller particle size range of 100 nm. Nanoparticles of this size can expose sufficient active sites, which is beneficial to the improvement of catalytic activity.

[0034] (2) Before high-temperature calcination and decomposition, the zeolite imidazolate framework material (ZIF) crystal precursor is impregnated with an inorganic salt solution. Under an inert atmosphere and high temperature, the inorganic salt will melt to form a molten salt that is coated on the surface of the Co-NC nanoparticles, which can effectively inhibit the agglomeration and sintering between the nanocrystals, so that they always maintain a highly dispersed state. The obtained cobalt-nitrogen-carbon material has a small particle size, a large specific surface area, a high pore volume, and a high electrocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a scanning electron microscope image (SEM) of the sample CoNC-1 prepared according to Example 1 of the present invention;

[0036] Figure 2 is a scanning electron microscope image of the sample CoNC-ET prepared according to Comparative Example 1 of the present invention;

[0037] Figure 3 is a scanning electron microscope image of the sample CoNC-EG prepared according to Comparative Example 2 of the present invention;

[0038] Figure 4is an X-ray diffraction pattern (XRD) of sample CoNC-1 prepared according to Example 1 of the present invention;

[0039] FIG5 is the electrochemical test results of Co-NC catalysts prepared according to the embodiments of the present invention and the comparative examples: Figure 5A It is linear sweep voltammetry (LSV); Figure 5B is cyclic voltammetry (CV). DETAILED DESCRIPTION

[0040] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0041] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0042] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0043] Embodiment 1:

[0044] Weigh 4.4g of cobalt nitrate and dissolve it in 150mL of ethylene glycol solution to obtain a cobalt salt solution. Weigh 7.5g of the organic ligand 2-methylimidazole and dissolve it in 150mL of ethanol to obtain an organic ligand solution. Add the organic ligand solution to the cobalt salt solution, stir it vigorously to mix and evenly disperse it, and keep stirring vigorously for 1h to obtain a mixed solution, then transfer the mixed solution to a water bath and react in a water bath at 60℃ for 2h. After the water bath, the sample is centrifuged and washed several times with ethanol to remove excess 2-methylimidazole and precursor salt, and then air-dried at 60℃. The dried sample is immersed in 100mL of potassium chloride methanol solution, where the concentration of potassium chloride is 0.06g / mL, the immersion time is 2h, and then air-dried at 60℃ to obtain a light purple solid powder. The obtained solid powder is spread on the bottom of the crucible, transferred to a tubular furnace, passed through an inert gas Ar for protection, and calcined and decomposed at 900℃. Finally, the obtained carbonized sample was dispersed in water and allowed to stand for 1 h, potassium chloride was removed, and the sample was filtered and dried by air blast to obtain a Co-NC sample, which was labeled as CoNC-1.

[0045] Embodiment 2:

[0046] Weigh 2.1g of cobalt chloride and dissolve it in 150mL of propylene glycol solution to obtain a cobalt salt solution. Weigh 3g of the organic ligand 5,6-dimethylbenzimidazole and dissolve it in 150mL of methanol to obtain an organic ligand solution. Add the organic ligand solution to the cobalt salt solution, stir it vigorously to mix and evenly disperse it, and keep stirring vigorously for 0.5h, then transfer the mixed solution to a water bath and react in a water bath at 60℃ for 3h. After the water bath, the sample is vacuum filtered and separated, and washed with ethanol several times to remove excess 2-methylimidazole and precursor salt, and then dried by blast at 50℃. The dried sample is immersed in 100mL of potassium chloride ethanol solution, where the concentration of potassium chloride is 0.02g / mL, the immersion time is 3h, and then dried by blast at 60℃ to obtain a light purple solid powder. The obtained solid powder is spread on the bottom of the crucible, transferred to a tubular furnace, passed with inert gas Ar protection, and calcined and decomposed at 800℃. Finally, the obtained carbonized sample was dispersed in water and allowed to stand for 1.5 h, potassium chloride was removed, and the sample was filtered and dried by air blast to obtain a Co-NC sample, which was labeled as CoNC-2.

[0047] Embodiment 3:

[0048] Weigh 10.6g of cobalt acetate and dissolve it in 150mL of glycerol solution to obtain a cobalt salt solution. Weigh 15g of the organic ligand 2-methylimidazole and dissolve it in 150mL of ethanol to obtain an organic ligand solution. Add the organic ligand solution to the cobalt salt solution, stir it vigorously to mix and evenly disperse it, and keep stirring vigorously for 1.5h, then transfer the mixed solution to a water bath and react in a water bath at 60℃ for 4h. After the water bath, the sample is separated by cross-flow filtration, washed with ethanol several times to remove excess 2-methylimidazole and precursor salt, and dried by blast at 70℃. The dried sample is immersed in 100mL of sodium chloride methanol solution, in which the concentration of potassium chloride is 0.1g / mL, the immersion time is 4h, and then dried by blast at 60℃ to obtain a light purple solid powder. The obtained solid powder is spread on the bottom of the crucible, transferred to a tubular furnace, passed through an inert gas Ar protection, and calcined and decomposed at 850℃. Finally, the obtained carbonized sample was dispersed in water and allowed to stand for 2 h, potassium chloride was removed, and the sample was filtered and dried by air blast to obtain a Co-NC sample, which was labeled as CoNC-3.

[0049] Comparative Example 1: (The difference from Example 1 is that no molten salt protection treatment is added)

[0050] Weigh 4.4 g of cobalt nitrate and dissolve it in 150 mL of ethylene glycol solution to obtain a cobalt salt solution. Weigh 7.5 g of the organic ligand 2-methylimidazole and dissolve it in 150 mL of ethanol to obtain an organic ligand solution. Add the organic ligand solution to the cobalt salt solution, stir it vigorously to mix and evenly disperse it, and keep stirring vigorously for 1 hour to obtain a mixed solution, then transfer the mixed solution to a water bath and react it in a water bath at 60 ° C for 2 hours. After the water bath, the sample is centrifuged and washed several times with ethanol to remove excess 2-methylimidazole and precursor salt, and then dried at 60 ° C. Spread the obtained solid powder on the bottom of the crucible, transfer it to a tubular furnace, pass inert gas Ar protection, and calcine and decompose at 900 ° C to obtain a Co-NC sample, marked as CoNC-ET.

[0051] Comparative Example 2: (The difference from Example 1 is that the solvent of the organic ligand solution is ethylene glycol instead of ethanol)

[0052] Weigh 4.4g of cobalt nitrate and dissolve it in 150mL of ethylene glycol solution to obtain a cobalt salt solution. Weigh 7.5g of the organic ligand 2-methylimidazole and dissolve it in 150mL of ethylene glycol to obtain an organic ligand solution. Add the organic ligand solution to the cobalt salt solution, stir it vigorously to mix and evenly disperse it, and keep stirring vigorously for 1h, then transfer the mixed solution to a water bath and react it in a water bath at 60℃ for 2h. After the water bath, the sample is centrifuged and washed several times with ethanol to remove excess 2-methylimidazole and precursor salt, and then air-dried at 60℃. The dried sample is immersed in 100mL of potassium chloride methanol solution, where the concentration of potassium chloride is 0.06g / mL, the immersion time is 2h, and then air-dried at 60℃ to obtain a light purple solid powder. The obtained solid powder is spread on the bottom of the crucible, transferred to a tubular furnace, passed through an inert gas Ar for protection, and calcined and decomposed at 900℃. Finally, the obtained carbonized sample was dispersed in water and allowed to stand for 1 h, potassium chloride was removed, and the sample was filtered and dried by air blast to obtain a Co-NC sample, which was labeled as CoNC-EG.

[0053] Test Results

[0054] 1. Scanning electron microscopy results

[0055] like Figure 1-3 As shown in the figure, the scanning electron microscope photos of CoNC-1, CoNC-ET and CoNC-EG prepared by the methods of Example 1, Comparative Example 1 and Comparative Example 2 are respectively. Figure 1-3 It can be seen that the CoNC-1 sample prepared in Example 1 ( Figure 1 ) are uniform in size, with a particle size of about 100 nm, in a highly dispersed state, without obvious agglomeration, and with good crystallinity, which are beneficial to the improvement of catalytic performance; CoNC-ET ( Figure 2 ) The particle size is relatively large, the particle size is >400nm, which is much higher than the size of the sample in the embodiment, and the particles are severely sintered and agglomerated, which is not conducive to the full contact between the active sites and O2, affecting the catalytic activity; CoNC-EG prepared in Comparative Example 2 ( Figure 3 ), the particle size is smaller than that of CoNC-ET in comparative example 1, but the crystallinity is poor and the particle size is not uniform. The above scanning electron microscopy results show that the use of ethanol / methanol, polyol mixed solvent and inorganic salt solution for immersion treatment can effectively improve the dispersibility and crystallinity of nanoparticles, thereby improving their electrocatalytic performance.

[0056] 2. N2 adsorption and desorption test results

[0057] CoNC-1, CoNC-ET and CoNC-EG were further subjected to N2 adsorption and desorption tests. The test results are shown in Table 1 below:

[0058] Table 1 N2 adsorption and desorption test results of Example 1 and Comparative Examples 1 and 2.

[0059]

[0060] The above test results show that the specific surface area of ​​CoNC-1 prepared in Example 1 is much higher than that of CoNC-ET in Comparative Example 1, which is consistent with the test results of SEM. 3 / g), which is conducive to the full contact between O2 and the active sites in the catalyst, thereby improving the catalytic efficiency. Comparative Example 2 also has a higher specific surface area (352.7m 2 / g), but the pore volume is low, which is not conducive to mass transfer in the catalytic process.

[0061] 3. X-ray diffraction results

[0062] Figure 4 The X-ray diffraction pattern (XRD) of CoNC-1 prepared in Example 1 is shown. Figure 4 The diffraction peaks of show that CoNC-1 only includes pure carbon and cobalt phases, in which cobalt is in the metallic cobalt phase, indicating that the precursor has been completely decomposed during calcination, without any precursor residue, and the obtained Co-NC product has a high purity.

[0063] 4. Oxygen reduction activity test results

[0064] The oxygen reduction activity of CoNC prepared in the embodiment and the comparative example was further tested, mainly by electrochemical testing. The results are shown in FIG5 , where: Figure 5A This is the linear sweep voltammetry (LSV) test result. Figure 5B It is the test result of cyclic voltammetry (CV). As can be seen from Figure 5, the half-wave potentials of CoNC-1, CoNC-2 and CoNC-3 prepared in Examples 1, 2 and 3 are higher than those in the comparative example, corresponding to higher electrocatalytic oxygen reduction (ORR) activity. At the same time, it can be seen that the limiting current of the embodiment is also much higher than that of the comparative example. This is because the particle size of the embodiment is small and highly dispersed, which can better contact with O2 and effectively improve the catalytic activity of Co-NC, which is consistent with the SEM and N2 adsorption and desorption test results.

[0065] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing a cobalt-nitrogen-carbon material with high electrocatalytic performance, characterized in that: The preparation method comprises the following steps: (1) Preparing a cobalt salt solution using a polyol as a solvent; (2) preparing an organic ligand solution, using ethanol or methanol as the solvent; (3) mixing the organic ligand solution and the cobalt salt solution to react; (4) performing solid-liquid separation on the reaction system after the reaction to obtain a zeolite imidazolate framework structure material; (5) impregnating the obtained zeolite imidazolate framework material with an inorganic salt solution; (6) Under the protection of an inert gas, calcining and decomposing the impregnated zeolite imidazolate framework material at a high temperature to obtain a crude Co-NC product; (7) purifying the crude Co-NC product to remove inorganic salts and impurities therein to obtain pure Co-NC powder; The inorganic salt in step (5) is selected from at least one of potassium chloride and sodium chloride.

2. The preparation method according to claim 1, characterized in that: The cobalt salt in step (1) is selected from at least one of cobalt nitrate, cobalt chloride, cobalt bromide, cobalt acetate and cobalt sulfate; And / or, the cobalt ion concentration in the cobalt salt is 0.05-0.5 mol / L.

3. The preparation method according to claim 1, characterized in that: The polyol in step (1) is at least one selected from ethylene glycol, propylene glycol, glycerol, and butylene glycol.

4. The preparation method according to claim 1, characterized in that: The organic ligand in step (2) is selected from at least one of 2-methylimidazole and 5,6-dimethylbenzimidazole, And / or, the concentration of the organic ligand in the solution is 0.01-0.1 g / mL.

5. The preparation method according to claim 1, characterized in that: The mixing reaction in step (3) specifically includes: The organic ligand solution and the cobalt salt solution are fully mixed by vigorous stirring for 0.5 to 1.5 hours to obtain a mixed solution, and then the mixed solution is reacted in a water bath at 60 to 80° C. for 0.5 to 4 hours.

6. The preparation method according to claim 1, characterized in that: The solid-liquid separation in step (4) is selected from at least one of centrifugal separation, vacuum filtration, and cross-flow filtration.

7. The preparation method according to claim 1, characterized in that: After the solid-liquid separation in step (4), the obtained zeolite imidazolate framework material is further washed with ethanol; And / or, the zeolite imidazolate framework material is dried by forced air at 50-70°C.

8. The preparation method according to claim 1, characterized in that: The concentration of the inorganic salt in the solution is 0.01-0.1 g / mL; And / or, the solvent of the inorganic salt solution is selected from at least one of methanol and ethanol; And / or, the immersion treatment time is 2 to 4 hours.

9. The preparation method according to claim 1, characterized in that: The inert gas in step (6) is selected from at least one of argon, nitrogen and helium; And / or, the high temperature calcination temperature is 800-900°C.

10. The preparation method according to claim 1, characterized in that: The purification treatment in step (7) specifically includes: dispersing the crude Co-NC product in water, standing for 1 to 2 hours, separating the solid and the liquid, and drying.

Citation Information

Patent Citations

  • Graphite phase carbide nitride nanosheet / ZiF-67 lamellar structure composite material

    CN106925330A

  • Preparation method of nitrogen-doped carbon-loaded cobalt catalyst

    CN114345387A

  • Monatomic cobalt-loaded tubular carbon nitride catalyst as well as preparation method and application thereof

    CN114534759A

  • Preparation of cobalt-carbon-nitrogen hollow polyhedral catalyst and application of cobalt-carbon-nitrogen hollow polyhedral catalyst in degradation of emerging pollutants

    CN114713259A

  • Non-noble metal catalyst as well as preparation method and application thereof

    CN114551905A